Progress Towards Elimination of Hepatitis C Infection Among People Who Inject Drugs in Australia: The ETHOS Engage Study. (18th May 2020) - Valerio, Heather; Alavi, Maryam; Silk, David; Treloar, Carla; Martinello, Marianne; Milat, Andrew; Dunlop, Adrian; Holden, Jo; Henderson, Charles; Amin, Janaki; Read, Phillip; Marks, Philippa; et al.
Abstract: Background: Evaluating progress towards hepatitis C virus (HCV) elimination is critical. This study estimated prevalence of current HCV infection and HCV treatment uptake among people who inject drugs (PWID) in Australia. Methods: The Enhancing Treatment of Hepatitis C in Opioid Substitution Settings Engage is an observational study of PWID attending drug treatment clinics and needle and syringe programs (NSPs). Participants completed a questionnaire including self-reported treatment history and underwent point-of-care HCV RNA testing (Xpert HCV Viral Load Fingerstick; Cepheid). Results: Between May 2018 and September 2019, 1443 participants were enrolled (64% injected drugs in the last month, 74% receiving opioid agonist therapy [OAT]). HCV infection status was uninfected (28%), spontaneous clearance (16%), treatment-induced clearance (32%), and current infection (24%). Current HCV was more likely among people who were homeless (adjusted odds ratio, 1.47; 95% confidence interval, 1.00–2.16), incarcerated in the previous year (2.04; 1.38–3.02), and those injecting drugs daily or more (2.26; 1.43–2.42). Among those with previous chronic or current HCV, 66% (n = 520/788) reported HCV treatment. In adjusted analysis, HCV treatment was lower among females (.68; .48–.95), participants who were homeless (.59; .38–.96), and those injecting daily or more (.51; .31–.89). People aged ≥45 years (1.46; 1.06–2.01) and people receiving OAT (2.62; 1.52–4.51) were more likely to report HCV treatment. Conclusions: Unrestricted direct-acting antiviral therapy access in Australia has yielded high treatment uptake among PWID attending drug treatment and NSPs, with a marked decline in HCV prevalence. To achieve elimination, PWID with greater marginalization may require additional support and tailored strategies to enhance treatment. Abstract : Among this population of people who inject drugs in Australia, 24% were currently infected with hepatitis C virus. Of those who were ever infected, 66% had received treatment. Enhancing treatment uptake in key subpopulations is required to achieve elimination.